2017
DOI: 10.1101/210070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forest Dormouse (Dryomys nitedula) populations in southern Italy belong to a deeply divergent evolutionary lineage

Abstract: The Forest Dormouse (Dryomys nitedula) is a small rodent with a wide, albeit severely fragmented distribution, ranging from central Europe to central Asia. Within the Italian region, D. nitedula populations are restricted to forested mountain areas of two largely disconnected regions, the eastern Alps and the Calabria region, where two distinct subspecies (D. nitedula intermedius and D. nitedula aspromontis, respectively) have been described on the basis of phenotypic characters (i.e., fur colour). Here we ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…Previous studies did not show substantial cytogenetic and morphometric differences between the disjoined population of Calabria with those of the Alps (Civitelli et al 1995. Recent molecular studies (Bisconti et al 2017) have shown that the subspecies of Calabria D. nitedula aspromontis (see distribution in Fig. 5) is a deeply divergent evolutionary lineage representing a new endemic taxon to Italy.…”
Section: Biogeographia 33: 19-31mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies did not show substantial cytogenetic and morphometric differences between the disjoined population of Calabria with those of the Alps (Civitelli et al 1995. Recent molecular studies (Bisconti et al 2017) have shown that the subspecies of Calabria D. nitedula aspromontis (see distribution in Fig. 5) is a deeply divergent evolutionary lineage representing a new endemic taxon to Italy.…”
Section: Biogeographia 33: 19-31mentioning
confidence: 99%
“…The amount of sequence divergence suggested a divergence time between the Calabrian and north Italian population around one million years ago (i.e. the Early Pleistocene) (Bisconti et al 2017). Altobello, 1926.…”
Section: Biogeographia 33: 19-31mentioning
confidence: 99%
“…The Calabrian region is a well-known glacial refugium for temperate species in peninsular Italy, 8 and provides one of the best examples of highly sub-structured refugia, a scenario known as refugia-within-refugia (Gomez & Lunt, 2007). Indeed, for most of the temperate species studied to date in this area, the Calabrian region provided suitable albeit fragmented habitats through most of Pleistocene, allowing long-term survival of relict populations (Bisconti et al, 2018;Senczuk, Colangelo, De Simone, Aloise & Castiglia, 2017). Accordingly, the Early-Middle Pleistocene origin of Calabrian bank vole populations was suggested by both molecular dating and fossil evidence (Colangelo et al, 2012;Sala & Masini 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Strong genetic differentiation and high intra-specific variation of Calabrian populations is a fairly common pattern in both animal and plant species (Bisconti et al, 2018;Canestrelli et al, 2006;Canestrelli, Cimmaruta & Nascetti, 2008;Canestrelli, Aloise, Cecchetti & Nascetti 2010;Canestrelli, Sacco & Nascetti, 2012;Chiocchio, Bisconti, Zampiglia, Nascetti & Canestrelli, 2017;Hewitt, 2011;Vega, Amori, Aloise, Cellini, Loy & Searle, 2010). The Calabrian region is a well-known glacial refugium for temperate species in peninsular Italy, 8 and provides one of the best examples of highly sub-structured refugia, a scenario known as refugia-within-refugia (Gomez & Lunt, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation